THE ROLE OF MENTORSHIP IN A SASKATCHEWAN CROSS-CULTURAL TEACHER EDUCATION PROJECT - Ward, Angela (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1998)
ABSTRACT. This paper describes a cross-cultural teacher education project which took place in Saskatchewan. A teacher team mentored a group of upper-level education students working in multicultural classrooms in the Province of Saskatchewan. The evolving participant structures of the research moved beyond the originally proposed mentorship model. RÉSUMÉ. Cet article décrit un projet transculturel de formation des maîtres réalisé en Saskatchewan. Une équipe d'enseignants a conseillé un groupe d'étudiants en dernière année de sciences de l'éducation travaillant dans des classes multiculturelles en Saskatchewan. Les structures de participation évolutives de la recherche ont dépassé le cadre initial du modèle de mentorat proposé.